MEGAEVENTOS ESPORTIVOS E A EDUCAÇÃO FÍSICA ESCOLAR: COM A PALAVRA, OS PROFESSORES DA EDUCAÇÃO BÁSICA - MARCONDES, FRANCIER (2016)
Brazil is experiencing a significant moment for the sport: the achievement of called Mega events Sports. With this, there is a remarkable concern of a political, economic and social committee which causes a series of responsibilities, agonies and unrest in relation to the possible influences with the legacies and collections that are directed to physical education at school that many times is treated as the base of the pyramid national sports. In this context, the present study aimed to understand how the teachers working in Basic Education in the municipality of Pitanga, PR, establish relations between the teaching of Physical Education and Sports Mega events, in other words, to examine the senses that guide the teaching action in his practice during this period. Was performed, initially, a bibliographic review as a basis for the understanding of the multi-faceted perspective which constitutes the sports phenomenon, either as an expression of income/spectacle or as a leisure activity and its Insert as content of physical education at school. The survey took over the qualitative nature with descriptive purpose and explanatory notes, by means of semi-structured interviews, carried out with 12 teachers from the public school network of the Municipality of Pitanga, PR. The analysis was performed, with interpretative character approaching the regional reality experienced in the school environment with culture established in the social relations of group, allowing you to identify distinct particularities in the understandings of teachers about the sports phenomenon face of symbolic loads that Mega events bring to their physical education classes, in order to establish their relations from a diversity of look on elements that constitute the plans and interventions of the teachers in their teaching practice.